1990
DOI: 10.1002/hep.1840110303
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence factors studied by percutaneous transpepatic portography before and after endoscopic sclerotherapy for esophageal varies

Abstract: High recurrence and rebleeding rates have been reported when endoscopic sclerotherapy has been performed on patients with esophageal varices. We studied the relationship between embolization range and recurrence rate in 26 patients in whom percutaneous transhepatic portography was carried out before and after sclerotherapy. Patients were divided into complete and incomplete embolization groups. The complete embolization group consisted of 16 patients whose esophageal varices had disappeared and in whom emboliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…2). We reported previously [7]that the recurrence rates of esophageal varices within 2 years after EE with complete and incomplete embolization of supply routes were 6.7 and 70%, respectively. Because of this result, we consider that complete EE is the first choice for the treatment of esophageal varices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). We reported previously [7]that the recurrence rates of esophageal varices within 2 years after EE with complete and incomplete embolization of supply routes were 6.7 and 70%, respectively. Because of this result, we consider that complete EE is the first choice for the treatment of esophageal varices.…”
Section: Discussionmentioning
confidence: 99%
“…Their method tends to be inferior to endoscopic variceal ligation [6]because few endoscopists can accurately inject a sclerosant intravariceally into the blood supply. Because the recurrence rate within 2 years after EE was much lower with complete embolization of varix-associated supply routes than after incomplete embolization [7], we believe that the embolization of all associated supply routes is essential for the treatment of varices. EE requires knowledge of the portoazygos venous anatomy and quick identification of the anatomy on endoscopic varicography.…”
Section: Introductionmentioning
confidence: 99%
“…This method tends to be inferior to endoscopic variceal ligation [3]because few endoscopists can inject sclerosant intravariceally into the blood supply accurately. Because the recurrence rate within 2 years after EE was much lower with complete embolization [7], we believe that the embolization of all associated supply routes is essential for the treatment of varices.…”
Section: Discussionmentioning
confidence: 99%
“…We have used the latter method, known as endoscopic embolization (EE). Previously, we have reported that complete embolization of esophageal varices and their blood supply might help to reduce the rate of recurrence [7]. However, the portal hemodynamic changes following EE have yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…EVL and extravariceal EIS both eradicate varices locally, with no effect on interconnecting perforating or feeding vessels [41] . Takase et al [45] concluded that feeder vessels must be obliterated to prevent recurrence.…”
Section: Combination Of Endo�copic Injection �Clerotherapy and Endo�cmentioning
confidence: 99%